Clinical Findings of Melanoma-Associated Retinopathy with anti-TRPM1 Antibody - Yoichiro Shinohara; Ryo Mukai; Shinji Ueno; Hideo Akiyama (Case Reports in Ophthalmological Medicine)
Introduction. We report the clinical features and clinical course of melanoma-associated retinopathy (MAR), in which autoantibodies against the transient receptor potential cation channel subfamily M member 1 (TRPM1) were detected. Case Presentation. A 74-year-old man was referred to our hospital for treatment of bilateral vision loss. The best-corrected visual acuity was 20/100 in the right eye and 20/200 in the left eye. His electroretinogram (ERG) showed a reduced b-wave and a normal dark-adapted a-wave in both eyes. Optical coherence tomography (OCT) revealed loss of the interdigitation zone in both eyes. We strongly suspected MAR based on the markedly reduced b-wave in the ERG and a history of intranasal melanoma. The diagnosis was confirmed after autoantibodies against TRPM1 were detected in his blood serum. Fifteen months later, his ERG remained unchanged, and OCT showed bilateral cystic changes in the internal nuclear layer. The visual acuity in both eyes also remained unchanged. Conclusions. Anti-TRPM1 autoantibodies were detected in a patient diagnosed with MAR who had negative flash ERG and retinal microstructural abnormalities, and the impairment did not recover during the follow-up period. Identification of anti-TRPM1 antibodies was helpful in confirming the diagnosis of MAR.